Brucellosis in sheep and goats from extensive and intensive management farms in Lara state, Venezuela (Ágora de Heterodoxias, 2016)
The aim of this study was to determine the percentage of seropositivity to brucellosis in sheep and goats from farm with intensive and extensive management in Lara state. A total of 400 goats with over 6 months old from 21 farms and all sheep (169) of the same age living with goats at these farms, were evaluated. From total samples of goats analyzed, 297 belonged to farms with intensive management and 103 to extensive. About sheep analyzed, 118 belonged to farms with intensive management and 51 from extensive. Serum samples were obtained from animals and they were processed in lab by conventional testing Card Test and Competitive ELISA (cELISA) for brucellosis. As result of sera tested by competitive ELISA test, 40 goats (13.4%) were positive in intensive farms and 3 goats (2.9%) were positive in extensive farms. With regard to sheep, 23 animals (19%) were positive in intensive farms and 8 animals (15.7%) were positive in extensive farms. None of the sera tested positive by cELISA test resulted positive by conventional Card Test, so this test was not useful for the diagnosis of brucellosis in these species unlike cELISA. Goats showed positive signs of infertility as lower pregnancy rates and fewer deliveries per year, but no abortions. It is concluded that Brucella infection is present in sheep and goats in this town.
Keywords: Brucellosis; goats; sheep; ELISAc; Card Test